2016
DOI: 10.1080/00220388.2016.1171847
|View full text |Cite
|
Sign up to set email alerts
|

Does the Heterogeneity of Project Implementers Affect the Programme Participation of Beneficiaries?: Evidence from Rural Cambodia

Abstract: This study employs the dataset collected for the assessment of a post-harvest technology project in rural Cambodia and focuses on the heterogeneous preferences of project implementers, frequently overlooked in the literature on programme evaluation studies. We focus on the 'implementer effect' on the programme participation of the treated farmers. We demonstrate that the heterogeneous programme participation of ordinary farmers could be induced due to heterogeneity in the characteristics of the project staff. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, Wakano et al . () clearly showed that the degree of such informal contact is significantly associated with the number of training sessions ordinary farmers received from the key farmers.…”
Section: Differences In Definition or Perception Of ‘Training'mentioning
confidence: 96%
“…Indeed, Wakano et al . () clearly showed that the degree of such informal contact is significantly associated with the number of training sessions ordinary farmers received from the key farmers.…”
Section: Differences In Definition or Perception Of ‘Training'mentioning
confidence: 96%